Answer:
3+sqrt(13/2)
3-sqrt(13/2)
Step-by-step explanation:
2 (x-3) ^2 =13
Divide each side by 2
2/2 (x-3) ^2 =13/2
(x-3) ^2 =13/2
Take the square root of each side
sqrt((x-3) ^2) =±sqrt(13/2)
x-3 = ±sqrt(13/2)
Add 3 to each side
x-3+3 = 3±sqrt(13/2)
x = 3±sqrt(13/2)
-4x+29? I think that's what you're asking.
From the steps shown in the table given, we can conclude that: D. in solving the equation, the subtraction property of equality was not applied.
<h3>What is the Subtraction Property of Equality?</h3>
If a + b = c, to apply the subtraction property of equality so that b is moved to the other side of the equation, we would have:
a + b - b = c - b
a = c - b
Thus, from the table given, the none of the steps showed that the subtraction property of equality was applied in solving the equation, so, the answer is: D.
Learn more about the subtraction property of equality on:
brainly.com/question/1601404
#SPJ1
Answer:
45 mugs
Step-by-step explanation:
she already has sold 116 mugs and 50% would be 161 soooo 161-116=45 more mugs